Effects of inspiratory muscle training on lung function parameter in swimmers: a systematic review and meta-analysis - Carvajal-Tello, N.; Ortega, J. G.; Caballero-Lozada, A. F.; Devia-Quiñonez, M. J.; González-Calzada, I.; Rojas-Hernández, D.; Segura-Ordoñez, A. (Frontiers in Sports and Active Living, 2024)
Background This systematic review and meta-analysis aimed to assess the impact of inspiratory muscle training (IMT) on lung function parameters (MIP, MEP, FEV1, and FVC) between both elite and non-elite swimmers.